THE ATHYRIDOIDS OF THE TRANSITIONAL BEDS BETWEEN BELLEROPHON AND WERFEN FORMATIONS (UPPERMOST PERMIAN, SOUTHERN ALPS, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The transitional beds between Bellerophon and Werfen Formations, few centimetres thick and latest Permian in age, contain a brachiopod fauna with a relatively rich athyridoid assemblage, among which Janiceps is the most common and characteristic genus. The internal morphology of the type species (J. peracuta) is here described for the first time, and a taxonomical revision of the South Alpine species is proposed. The new subfamily Janicepsinae is proposed, which contains Janiceps and the new genus Comelicothyris. Among the latter genus, Comelicothyris laterosulcata n. sp. is suggested. Lectotypes are selected and illustrated for Spirigera janiceps Stache, S. confinalis Stache, S. bipartita Stache, S. ? archimedis Stache, Spirifer ? sextensis Stache, Athyris irregularis Merla, A. semilunaris Merla, and A janiceps var globulus Merla. The athyridoids of the transitional beds are characterized by a broad morphological variability which induced past authors to create many species and ìvarietiesî generally on the bais of a single or few individuals. As concerns Janiceps, only four species-versus the 14 species and 7 ìvarietiesî cited in the literature of the Souther Alps-are here considered valid (J. peracuta (Stache), J. cadorica (Stache), J. papilio (Stache), and J. bipartita (Stache)). Besides other four species are identified here; these are Comelicothyris recticardinis (Merla), Septospirigerella ? sp., Spirigerellinae gen. et sp. indet., and Comelicania merlai Posenato.